Motivational counselling and cognitive behaviour therapy could reduce nicotine dependence risk among Nigerian adolescents (2010)
Cigarette smoking is a serious problem worldwide with enormous psychological implications among adolescents. Despite risk of smoking, intervention strategies to address this problem are inadequate in Nigeria. This study was therefore designed to determine the relative efficacy of Cognitive-Behavioural Therapy (CBT) and Motivational Interviewing Supportive (MIS) counselling in reducing adolescents' nicotine dependence risk. Phase one of the study facilitated the documentation of code names, addresses, phone numbers, and school codes of all the participants. Participants who scored on the mean and above on the Nicotine Dependence Scale (NDS) in the first phase and expressed willingness to participate in the study were recruited for the intervention phase. Twenty-jive participants (20 males and 5 females each) were assigned to three intervention conditions, CBl; MIS and Waiting List Control Group (WLCG). ANCOVA results showed that adolescents in the two intervention groups reported significant reduction in the number of cigarettes smoked than those on the WLCG: F(2, 60) = 29.61, P < .05). Follow-up assessment showed that while adolescents exposed to CBT reported significant reduction in the number of cigarettes smoked at one month evaluation (P < .05), such effect was no longer observed at the three-month evaluation. Conversely, while there was no significant reduction in the number of cigarettes smoked by adolescents exposed to MIS at one month, there was a significant reduction in the number of cigarettes smoked at three-month evaluation (P < .05). Adolescents who were nicotine dependent benefited from the two psychological based intervention strategies for risk reduction. It is therefore recommended that such intervention programs should be incorporated in the school curriculum.